2014
DOI: 10.1111/all.12437
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis: guidelines from the European Academy of Allergy and Clinical Immunology

Abstract: Anaphylaxis is a clinical emergency, and all healthcare professionals should be familiar with its recognition and acute and ongoing management. These guidelines have been prepared by the European Academy of Allergy and Clinical Immunology (EAACI) Taskforce on Anaphylaxis. They aim to provide evidence-based recommendations for the recognition, risk factor assessment, and the management of patients who are at risk of, are experiencing, or have experienced anaphylaxis. While the primary audience is allergists, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
1,012
6
156

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 914 publications
(1,213 citation statements)
references
References 121 publications
13
1,012
6
156
Order By: Relevance
“…Anaphylaxis is a serious, generalized or systemic, allergic or hypersensitivity reaction with sudden onset (minutes to a few hours) that can be life threatening or even fatal. [8][9][10][11][12] The target organs in humans often include the respiratory tract (70% of episodes) and less frequently the gastrointestinal (GI) organs (30-45% of episodes), heart and vasculature (10-45% of episodes) and central nervous system (CNS) (10-15% of episodes). 8 It is generally agreed that anaphylaxis may occur with or without cutaneous signs, even though these latter signs are frequent and occur in 80-100% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Anaphylaxis is a serious, generalized or systemic, allergic or hypersensitivity reaction with sudden onset (minutes to a few hours) that can be life threatening or even fatal. [8][9][10][11][12] The target organs in humans often include the respiratory tract (70% of episodes) and less frequently the gastrointestinal (GI) organs (30-45% of episodes), heart and vasculature (10-45% of episodes) and central nervous system (CNS) (10-15% of episodes). 8 It is generally agreed that anaphylaxis may occur with or without cutaneous signs, even though these latter signs are frequent and occur in 80-100% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…4). 1, 31, 32, 33 Early injection of adrenaline for anaphylaxis, defined as injection before ER arrival, can significantly reduce the likelihood of hospital admission, as compared with initial injection after arrival at the ER 34. Although no human studies regarding the timing of treatment for anaphylaxis could be found, analysis of 92 deaths related to anaphylaxis showed that adrenaline was given prior to cardiac arrest in only 22 of the cases (24%) 35.…”
Section: Initial Treatment Of Anaphylaxismentioning
confidence: 99%
“…Most international anaphylaxis guidelines recommend injection of adrenaline by the intramuscular route in the mid‐anterolateral thigh at a dose of 0.01 mg/kg of a 1:1,000 (1 mg/mL) solution, up to a maximum of 0.5 mg in adults (0.3 mg in children). Depending on the severity of the episode and the response to the initial injection, the dose can be repeated every 5–15 min, as required 1, 31, 33, 36. Intravenous adrenaline is an option in patients with severe hypotension or cardiac arrest unresponsive to intramuscular doses of adrenaline and fluid resuscitation 1.…”
Section: Initial Treatment Of Anaphylaxismentioning
confidence: 99%
See 2 more Smart Citations